Significado Tectônico dos Depósitos de Leques Aluviais da Formação Santa Bárbara (Eo-Paleozóico) na Região de Caçapava do Sul (RS, Brasil) - DE BORBA, ANDRÉ WEISSHEIMER; MIZUSAKI, ANA MARIA PIMENTEL (Pesquisas em Geociências, 2002)
<!-- .p { text-align: justify; } --> The alluvial fan deposits of Early Paleozoic Santa Bárbara Formation, located in Sul-rio-grandense Shield area of southernmost Brazil, have been analyzed here in terms of facies associations and tectonic significance. The investigated unit comprises conglomerates, sandstones, and siltstones, deposited probably under continental semi-arid climate conditions, in the post-collisional stages of Neoproterozoic Brasiliano/Pan-African Cycle. The location of the alluvial deposits suggests that the depositional locus of this sedimentary unit should probably consist of an individual and restricted fault-bounded basin, named here Santa Bárbara Basin. Its settling was controlled by the extensional and strike-slip reactivation of NE, NW, and N-S structures inherited from Brasiliano/Pan-African Cycle. Alluvial deposits located in the southwestern and northwestern borders show dominance of sheetflood processes in the alluvial fans deposition. On the other hand, the eastern border of Santa Bárbara Basin, named the “Caçapava paleohigh”, comprises the coarser alluvial deposits, with major occurrence of debris-flow features. This fact suggests a possible asymmetry of this basin. These eastern border deposits reveal, in the clast composition of the conglomerates, three main phases of denudation of “Caçapava paleohigh”. The basal conglomerates reflect a stage when this important topographic high was covered by andesites and metasedimentary rocks. Stratigraphically above, metavolcanic fragments compose the coarse deposits, while at the top of the package the conglomerate framework consists mainly of granitic clasts. This third stage reflects the exposure of the deeper parts of “Caçapava paleohigh”, and it can be positioned at the base of the unconformable Sequence III of Santa Bárbara Formation. The total inversion of braided fluvial axial filling system and the occurrence of intrabasinal debris-flow deposits suggest a strong tectonic event and possibly a significant time span at the base of Sequence III.a